Notes on the species of Perkinsiana (Polychaeta: Sabellidae) from Antarctica with the description of P. brigittae sp. nov. - Tovar-Hernández, María Ana; Yáñez-Rivera, Beatriz; Giangrande, Adriana; Gambi, Maria Cristina (Zootaxa, 2012)
Nine nominal species are known from Antarctica and adjacent waters that have been assigned to the genus Perkinsiana(Polychaeta: Sabellidae). Taxonomic notes for these species are provided. Currently, only six species are considered valid:Perkinsiana antarctica (Kinberg), P. decorata (Rullier), P. borsibrunoi Giangrande and Gambi, P. magalhaensis(Kinberg), P. milae Giangrande and Gambi and P. pusilla (Johansson); P. antarctica (Gravier) is incertae sedis; P. littoralis(Hartman) is a suggested synonym of P. magalhaensis (Kinberg) and P. antarctica (Gravier), while Potamilla antarcticachristenseni Augener probably belongs to the genus Notaulax. Perkinsiana is amended based on the presence of a palmatemembrane and radiolar flanges, and three types of abdominal chaetae. The new species Perkinsiana brigittae sp. nov. ishere described from collections taken by the U. S. Antarctic Research Program (USARP) at Wilkes Station. A taxonomic key for species of Perkinsiana from Antarctica is provided.